The impact of illiteracy on the assessment of cognition and dementia: a critical issue in the developing countries - Noroozian, Maryam; Shakiba, Alia; Iran-nejad, Shahrzad (International psychogeriatrics, 2014)
Dementia and Alzheimer's disease (AD) is considered a major public health challenge in this decade and in the future. Early detection of AD through appropriate screening tools would be valuable approach in facing the burden of disease specifically in developing societies with insufficient resources. Selecting a screening tool which is non-expensive, non-invasive and implementable by trained primary healthcare providers is the first and probably the most important step in detecting high risk individuals. The goal of this review is to address the key issues in assessment tools in developing countries with a high level of illiteracy. We set about a review on literature on the subject of cognitive function assessment among minorities, people with low or no education, and people who live in underdeveloped societies. We also reviewed the studies on validation of such tests in a new society. The most popular assessment tools are more or less biased by the level of education; not all of them are useful for any type of dementia as they assess only some domains of cognitive function. Even though people with lower level of education have a higher rate of developing dementia, cognitive function cannot be accurately assessed because of limitations of current available tools. It is strongly suggested that special attention be paid to assess them by functional scales and activity daily living scales. For a more efficient assessment, cognitive tests can also benefit from illustrative questions, proverbs, metaphors, traditions, religious rituals and historical events.